The MEXICAN 68 SEEN FROM THE SINALOENS PRESS - Sánchez Parra, Sergio Arturo; Gil Pérez, Anderson Paul (Revista de Historia Social y de las Mentalidades, 2019)
The Mexican 68 is analyzed as a historical process that was the result of the political crisis that the country experienced from the itineraries of a student movement that questioned the government and that in a short time moved the established order that did not allow social protests and demonstrations against the presidential figures and the single party. At the same time, these processes are auscultated from the Sinaloa press, taking as analytical newspapers El Sol de Sinaloa, El Sol del Pacifica and El Sol de Culiacán. To conclude, the press was an accomplice of the government by not showing the excesses of the police and army forces against the students, and instead, legitimizing the visions that equated the students with communists and traitors to the country.